MANIFESTASI IDENTITAS ISLAM SUKU BAJO DALAM NASKAH LONTARAK ASSALENNA BAJO - Benny Baskara (Universitas Gadjah Mada, 2011)
The Bajo people are known as the sea wanderers because they always wander the sea. However, aside from their unique characteristic as people of the sea, the Bajo are also known as Muslims. Therefore, Islam is an important element of their identity, either reflected in their daily life or written in the manuscript Lontarak Assalenna Bajo as the form of self-narration of their cultural history. Islam has been accepted through a continual process of negotiation and development.The Bajo people were not Muslim before they became sea wanderes. They received the influence of Islam from the land-bound people surrounding them as a result of interactions between the two groups.